Investigation of speech perception for patients with a cochlear implant supported with a hearing aid - Niewiarowicz, M.; Stieler, O.; Komar, D. (Archives of Acoustics, 2006)
The investigations were carried out for 5 listeners with a cochlear implant, 2 male and3 female at implantation age 13–62 years. The deafness for 4 subjects was recognized aspostlingual and for 1 – as perilingual. All listeners were using the hearing aid on the oppositeear to the implant. The speech intelligibility was determined in two cases: when transmissionwas only via the implant and when the hearing aid was also used. Additionally, the abilityof discrimination of male and female voices was performed. The presentation of tests wasconducted for three angles (0$^{°}$, −90$^{°}$ and+90$^{°}$) in relation to the listener’s head for the levelsequal to 50, 65 and 80 dB SPL. The Polish monosyllabic word tests (PRUSZEWICZ et al., [4])were applied. The improvement of the speech intelligibility was affirmed when the process ofhearing via the implant was supported with a hearing aid. The particularly essential differencesin the speech intelligibility was observed for angle +90$^{°}$ (HA-side). The results obtained inthe investigations show that acoustic compensation in the range of remaining audibility fieldin a great degree supports electrical hearing.